2018
DOI: 10.1039/c8nr05851b
|View full text |Cite
|
Sign up to set email alerts
|

Distinct autophagy-inducing abilities of similar-sized nanoparticles in cell culture and liveC. elegans

Abstract: Silicon nanoparticles, having the same size as the autophagy-inducing QDs, CDs and AuNPs, do not induce autophagy in vitro and in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 69 publications
1
7
0
Order By: Relevance
“…Caenorhabditis elegans (C. elegans) is a well-established small nematode model organism that has been used since the 1970s [63]. Unlike the traditional toxicity cell culture testing systems, C. elegans provide data from a whole animal with complete and metabolically active digestive, reproductive, endocrine, sensory, and neuromuscular systems [64]. Indeed, C. elegans research has been proved to be essential in the clarification of several basic aspects of biology, including apoptosis, autophagy, RNA interference, and miRNA function.…”
Section: Elegans Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Caenorhabditis elegans (C. elegans) is a well-established small nematode model organism that has been used since the 1970s [63]. Unlike the traditional toxicity cell culture testing systems, C. elegans provide data from a whole animal with complete and metabolically active digestive, reproductive, endocrine, sensory, and neuromuscular systems [64]. Indeed, C. elegans research has been proved to be essential in the clarification of several basic aspects of biology, including apoptosis, autophagy, RNA interference, and miRNA function.…”
Section: Elegans Modelmentioning
confidence: 99%
“…Regarding the nanomaterial-induced autophagy, C. elegans has been employed to identify and characterize the autophagy-regulating mechanism, and 139 conserved genes that regulate autophagy activity are identified, offering a framework for thorough dissection of the autophagy process [68]. Studies show that treatment of quantum dots (QDs), gold nanoparticles (AuNPs), and carbon dots (CDs) are able to induce massive autophagosome formation, autophagy related gene upregulation, and autophagy substrate degradation in cultured HeLa cells and in live C. elegans [64]. Due to the small size of C. elegans, it is very easy to track the autophagosome formation in real-time by simply using the fluorescence microscopy [69], making C. elegans a suitable model organism for the alternative nanotoxicity approach and providing great connection between in vitro and in vivo toxicity [69].…”
Section: Elegans Modelmentioning
confidence: 99%
“…And p62 interacts with LC3 and degrades during the fusion of autophagosomes and lysosomes, so there is a inverse correlation between the expression of p62 and autophagy activity (Ji et al, 2016). Autophagy and the whole process of autophagy flux should be monitored by combining multiple methods, such as TEM, LC3 and p62 expression in protein and gene level, rather than just one index (Wang et al, 2018).…”
Section: Main Mechanisms Of Cytotoxicity Induced By Three Kinds Of Qdsmentioning
confidence: 99%
“…They used four types of similar sized nanomaterials including silicon nanoparticles (SiNP), CdTe quantum dots, carbon dots, and AuNPs. They observed that unlike other nanomaterials tested, no autophagosome formation was detected in C. elegans with SiNP exposure, suggesting that the "nanoscale" size is not the determining factor for the nanomaterials to induce autophagy in C. elegans [41]. A recent microarray study showed that developmental changes in C. elegans following mercaptoundecanoic acid-coated AuNPs were related to differential gene expression in clec-174 (involved in cellular defense), cut-3 and fil-1 (both involved in body morphogenesis), dpy-14 (expressed in embryonic neurons), and mtl-1 (functions in metal detoxification and homeostasis) genes [42].…”
Section: Discussionmentioning
confidence: 97%
“…The cellular uptake and toxicity of nanoparticles mainly depend on their size, shape, and surface chemistry [38][39][40]. Wang et al [41] used the C. elegans model to understand whether the "nanoscale" size is the determining factor for the nanomaterials to induce autophagy. They used four types of similar sized nanomaterials including silicon nanoparticles (SiNP), CdTe quantum dots, carbon dots, and AuNPs.…”
Section: Discussionmentioning
confidence: 99%